Creating conditions for working collaboratively in discipline-based writing at a South African university - Dison, L; Moore, J. (Stellenbosch University, 2019)
Students’ academic literacy practices frequently do not prepare them for, or articulate with, the ways of thinking and practising within their chosen academic disciplines (Boughey, 2010; Clarence, 2010; Wingate & Tribble, 2012). There has been much debate about who should be responsible for responding to this ‘articulation gap’ (Bitzer, 2009) and how this should be done. In this paper, we posit the importance of working with students in the disciplines and draw on Lillis and Scott’s (2007) notion of transformative writing spaces to engage critically with disciplinary culture, norms and practices. We critique ‘remedial’ approaches to tertiary writing development that treat the articulation gap as a skills deficit that can be overcome by teaching a set of requisite academic literacy skills. We also suggest that increased collaboration between writing centres and discipline-based academic staff has helped to shift the deficit conception to more socially constructed approaches to writing development. We explore conditions in two discipline-specific writing centres that show how writing can be used as a way of engaging all students with core course concepts and in which writing development has been embedded within mainstream, substantive modules in order to facilitate epistemological access (Morrow, 2007) to both disciplinary content and writing in the discourse.
Keywords: writing centres; writing in the disciplines; transformation of higher education; academic literacies; epistemological access; writing consultants; assessment for learning; collaborative pedagogy